A proton exchange membrane water electrolysis anode catalyst, preparation method and application thereof
By loading IrOx on the surface of the Ti4O7 support of the proton exchange membrane water electrolytic anode catalyst and building a TiO2 layer, the problems of easy shedding of Ir nanoparticles and easy oxidation of Ti4O7 are solved, and efficient and stable catalytic performance is achieved.
Patent Information
- Application Number
- CN202310322554.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-29
AI Technical Summary
In the existing proton exchange membrane water electrolytic anode catalyst, Ir nanoparticles are prone to shedding and agglomeration during the reaction, and the Ti4O7 support is easily deeply oxidized under high oxidation potential, resulting in a decrease in catalytic activity.
Using post-oxidation heat treatment technology, IrOx is loaded on the surface of the conductive Ti4O7 carrier, and a dense TiO2 layer is constructed in the area not loaded by IrOx to form an IrOx/Ti4O7@TiO2 catalyst.
The utilization rate of precious metal Ir is improved, the interaction between IrOx and Ti4O7 is enhanced, the agglomeration and shedding of nanoparticles is avoided, and the deep oxidation of Ti4O7 is inhibited, thereby enhancing the stability and activity of the catalyst.
Smart Images

Figure CN116516406B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a proton exchange membrane water electrolysis anode catalyst, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) coupled with renewable energy can convert intermittently available wind power, hydropower, solar energy, etc. into high-energy-density hydrogen energy in remote areas, which is of great significance to the comprehensive utilization of renewable energy and shows a broad market space. The hydrogen evolution reaction (HER) occurs at the cathode of PEMWE, and the oxygen evolution reaction (OER) occurs at the anode. Compared with HER, OER has slow kinetics and requires highly active catalytic sites. At the same time, under the strong acidic and oxidizing conditions on the anode side, OER catalysts face the test of stability. Although Ir-based catalysts, as the catalytic materials with the most suitable activity and stability, have been commercially applied to a certain extent, the rare nature and high price of precious metals have greatly limited the large-scale application of PEMWE. Therefore, the development of efficient and stable OER catalysts with low Ir dosage is of great significance to promote the large-scale application of PEMWE.
[0003] At present, the development of supported Ir-based catalysts is an effective strategy to reduce the amount of precious metal Ir in membrane electrodes while improving catalytic activity and stability. In membrane electrodes, the performance of supported catalysts depends on the dispersion of catalytically active substances on the surface of the carrier, the strength of the interaction between the carrier and the catalytically active substances, and the conductivity and stability of the carrier itself. Studies have reported that small-sized Ir nanoparticles can be prepared on the surface of the carrier by polyol reduction, which can effectively improve the utilization rate of precious metal Ir. However, the Ir nanoparticles prepared by simple polyol reduction have the problem of falling off and agglomerating from the surface of the carrier during the reaction, indicating that the interaction between the carrier and the active substance still needs to be further strengthened. In addition, how to design a carrier that has both conductivity and stability is also a difficult problem that needs to be solved urgently.
[0004] As an oxide carrier with high electrical conductivity, Ti4O7 rich in oxygen defects has attracted the attention of researchers. However, it is prone to uncontrollable deep oxidation at high oxidation potentials, transforming into TiO2 with extremely poor conductivity, resulting in a decrease in the overall activity of the catalyst. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a proton exchange membrane water electrolysis anode catalyst, a preparation method and application thereof. The anode catalyst has a low content of precious metal iridium and has high catalytic activity and stability.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a proton exchange membrane water electrolysis anode catalyst, comprising a carrier Ti4O7 and IrOx and TiO2 supported on the Ti4O7;
[0008] Among them, 1<x≤2.
[0009] Preferably, the mass ratio of IrOx to Ti4O7 is (0.1-4):1.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned proton exchange membrane water electrolysis anode catalyst, comprising the following steps:
[0011] The Ti4O7 loaded with elemental iridium is heat-treated at 200-600° C. to obtain the anode catalyst.
[0012] Preferably, the atmosphere of the heat treatment is air atmosphere.
[0013] Preferably, the heating rate of the heat treatment is 0.5-10°C / min.
[0014] Preferably, the heat treatment time is 0.5 to 24 hours.
[0015] Preferably, the Ti4O7 loaded with elemental iridium is prepared by a polyol reduction method or a hydrogen reduction method.
[0016] In a third aspect, the present invention provides a proton exchange membrane water electrolysis anode catalyst slurry, comprising the anode catalyst, dispersant, binder and solvent involved in the above technical solution.
[0017] In a fourth aspect, the present invention provides a membrane electrode for proton exchange membrane water electrolysis, comprising an anode catalyst layer, a cathode catalyst layer, and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer;
[0018] The anode catalyst layer is prepared by subjecting the anode catalyst slurry to a film-forming treatment.
[0019] In a fifth aspect, the present invention provides a proton exchange membrane water electrolysis hydrogen production electrolytic cell, comprising the anode catalyst, anode catalyst slurry or membrane electrode involved in the above technical solution.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The anode catalyst provided by the present invention is to oxidize the Ir loaded on the surface of the carrier to IrOx (1<x≤2) by post-oxidation heat treatment of the conductive Ti4O7 carrier loaded with small-sized active Ir nanoparticles, and at the same time, to construct a dense TiO2 layer in the area on the surface of the Ti4O7 carrier that is not loaded with Ir, thereby obtaining the final anode catalyst. The amount of iridium in IrOx in the anode catalyst is reduced by one order of magnitude compared with the commercial sample, the cost is low, the utilization rate of the precious metal Ir is greatly improved, and the intrinsic stability of IrOx is better than that of elemental iridium, and the interaction with Ti4O7 is stronger, and it is not easy to agglomerate and fall off. At the same time, the presence of TiO2 can fill the area of Ti4O7 that is not coated by IrOx, thereby effectively inhibiting the deep uncontrollable oxidation of Ti4O7 to TiO2 during the operation of the proton exchange membrane water electrolysis hydrogen production device, thereby reducing the catalytic activity. Therefore, the anode catalyst has the advantages of low cost, high catalytic activity and good stability. In addition, the preparation method of the anode catalyst is simple, environmentally friendly, and suitable for large-scale industrial production, which can reach several hundred grams, laying the foundation for the large-scale preparation of low-cost, high-activity, and long-life proton exchange membrane water electrolysis hydrogen production anode catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of IrOx / Ti4O7@TiO2 obtained in Example 1;
[0023] Figure 2 TEM image of IrOx / Ti4O7@TiO2 obtained in Example 1;
[0024] Figure 3 The XRD spectrum of IrOx / Ti4O7@TiO2 obtained in Example 1;
[0025] Figure 4 This is a polarization test curve diagram of a proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with IrOx / Ti4O7@TiO2 as the anode catalyst obtained in Example 1;
[0026] Figure 5 This is a stability test curve of a proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled using IrOx / Ti4O7@TiO2 obtained in Example 1 as the anode catalyst. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In view of the problems in the prior art that Ir nanoparticles in the anode catalyst of proton exchange membrane water electrolysis are easy to fall off and agglomerate from the surface of the carrier during the reaction, and the Ti4O7 carrier is easy to undergo uncontrollable deep oxidation at a high oxidation potential, and is converted into TiO2 with extremely poor conductivity, resulting in a decrease in the overall activity of the catalyst, the present invention provides a proton exchange membrane water electrolysis anode catalyst, including a carrier Ti4O7 and IrOx and TiO2 loaded on the Ti4O7; wherein 1<x≤2. In the present invention, the higher the mass of the IrOx, the better the catalytic performance, but the cost will also increase accordingly. Therefore, the present invention preferably determines the mass ratio of IrOx to Ti4O7 to be (0.1~4):1, specifically 0.1:1, 0.5:1, 1:1, 2:1, 3:1 or 4:1, etc. The ratios in the remaining ranges are also within the protection scope of the present invention, and will not be repeated here.
[0029] SEM and TEM characterizations revealed that the anode catalyst surface was uniformly distributed with IrOx nanoparticles without obvious agglomeration. XRD testing revealed that the anode catalyst had a peak corresponding to IrO2, a peak corresponding to TiO2, and multiple diffraction peaks corresponding to Ti4O7, indicating that the catalyst did contain the carrier Ti4O7 and the IrO2 and TiO2 loaded on the carrier.
[0030] The present invention loads IrOx on the surface of a highly conductive Ti4O7 carrier and constructs a dense TiO2 layer, wherein the amount of iridium in IrOx is reduced by one order of magnitude compared to commercial samples, the cost is low, the utilization rate of the precious metal Ir is greatly improved, and the intrinsic stability of IrOx is better than that of elemental iridium, and the interaction with Ti4O7 is stronger, and it is not easy to agglomerate and fall off. At the same time, the presence of TiO2 can fill the area of Ti4O7 that is not coated with IrOx, thereby effectively inhibiting the deep uncontrollable oxidation of Ti4O7 to TiO2 during the operation of the proton exchange membrane water electrolysis hydrogen production device, thereby reducing the catalytic activity. The proton exchange membrane water electrolysis anode catalyst has the advantages of low cost, high catalytic activity and good stability.
[0031] The present invention also provides a method for preparing the above-mentioned anode catalyst, comprising the following steps:
[0032] The Ti4O7 loaded with elemental iridium is heat-treated at 200-600° C. to obtain the anode catalyst.
[0033] According to the present invention, the Ti4O7 loaded with elemental iridium can be prepared by a polyol reduction method or a hydrogen reduction method. The polyol reduction method or the hydrogen reduction method can be carried out according to methods well known to those skilled in the art, and specific reference can be made to the corresponding methods in patent CN202110259388 and document RSCAdv., 2017, 7, 31582-31587. In some embodiments of the present invention, a polyol reduction method is used to prepare Ti4O7 loaded with elemental iridium, and the polyol reduction method specifically includes the following steps: after mixing a surfactant, a Ti4O7 carrier and a reducing agent, the obtained suspension is mixed with an iridium source, and then a constant temperature reflux reaction is performed to obtain Ti4O7 loaded with elemental iridium. Wherein, the surfactant is any one or more of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC) or polyvinylpyrrolidone (PVP); the Ti4O7 carrier can be a general commercial product, and its particle size is 20 to 2000nm. In some embodiments of the present invention, the particle size is 100nm or 150nm; the reducing agent can be an alcohol reagent with reducing properties, which can be selected from ethylene glycol, propylene glycol, etc., preferably ethylene glycol; the iridium source is selected from any one or more of iridic acid, iridium trichloride, potassium chloroiridate, iridium acetate or iridium acetylacetonate. In some embodiments of the present invention, it is preferred to disperse the surfactant and the Ti4O7 carrier in the reducing agent, and the dispersion is preferably ultrasonically dispersed, and the dispersion time is preferably 0.5 to 5h, specifically 0.5h, 1h, 2h, 3h, 4h or 5h, etc., more preferably 0.5 to 2h. Then, the iridium source is added to the ultrasonic suspension under stirring conditions, ultrasonicated for 0.5-1h, and then stirred for 0.5-5h. After stirring, a constant temperature reflux reaction is carried out. The temperature of the constant temperature reflux reaction is preferably 120-220°C, which can be 120, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, more preferably 140-180°C, and the time is preferably 1-6h, more preferably 2-6h. In some embodiments of the present invention, the ratio of the Ti4O7 carrier to the reducing agent is 1:1000000 to 1:10, the ratio of the surfactant to the iridium source is 1:1 to 10:1, and the mass ratio of Ir to Ti4O7 is 1:9 to 9:1, specifically 1:9, 1:5, 1:1, 2:1, 4:1, 5:1, 7:1 or 9:1, etc. The remaining ratios within this range are also within the scope of protection of the present invention and will not be repeated here. In some embodiments of the present invention, after the reflux reaction is completed, the steps of cooling, centrifugal washing, drying, etc. are also included. The reagent for the centrifugal washing is preferably ethanol and / or water, and the drying condition is vacuum drying at 50 to 70°C, or freeze drying is selected.
[0034] According to the present invention, after obtaining Ti4O7 loaded with elemental iridium, the Ti4O7 loaded with elemental iridium is subjected to heat treatment at 200-600° C. to obtain the anode catalyst. During the heat treatment process, a heating rate that is too fast will cause the catalyst to be heated quickly and explode, and a heating rate that is too slow will cause the sample preparation cycle to be too long. Therefore, in some embodiments of the present invention, the heating rate is preferably controlled at 0.5 to 10°C / min, specifically 0.5°C / min, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min, etc., preferably 1 to 5°C / min, and Ti4O7 loaded with elemental iridium is heat-treated at 200 to 600°C, specifically 200°C, 250°C, 300°C, 320°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, preferably at 200 to 400°C in an air atmosphere for 0.5 to 24h, more preferably 0.5 to 12h, further preferably 0.5 to 8h, and then cooled to obtain the anode catalyst. The cooling method can be natural cooling or quenching. In some embodiments of the present invention, the heat treatment is preferably performed in a muffle furnace.
[0035] The preparation method of the above-mentioned anode catalyst provided by the present invention is simple and environmentally friendly. First, a polyol reduction method or a hydrogen reduction method is used to load small-sized active Ir nanoparticles on the surface of a conductive Ti4O7 carrier. After a later oxidation heat treatment, the obtained IrOx particles have no significant agglomeration, the utilization rate of the precious metal Ir is greatly improved, and the interaction between IrOx and the Ti4O7 carrier is effectively enhanced, avoiding the agglomeration and shedding of nanoparticles; at the same time, the dense TiO2 layer constructed on the surface of the conductive Ti4O7 carrier can effectively inhibit the deep uncontrollable oxidation of the Ti4O7 carrier, and improve the overall operation stability of the catalyst. The preparation method is easy to implement, which is conducive to industrial large-scale production. The mass of the product can reach several hundred grams, laying the foundation for the large-scale preparation of low-cost, high-activity, and long-life proton exchange membrane water electrolysis hydrogen production anode catalysts.
[0036] In the present invention, the proton exchange membrane water electrolysis anode catalyst is mixed with a dispersant, a binder and a solvent to prepare a proton exchange membrane water electrolysis anode catalyst slurry. The present invention has no particular restrictions on the dispersant, binder and solvent, and can be selected according to the routine selection of those skilled in the art as needed. For example, the dispersant can be a non-ionic surfactant, specifically selected from polyethylene glycol octylphenyl ether; the binder can be selected from any one or more of perfluorosulfonic acid resin, polytetrafluoroethylene or polyvinylidene fluoride-hexafluoropropylene copolymer; the solvent can be selected from any one or more of isopropanol, ethanol, nitrogen-methyl pyrrolidone, nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide or glycerol.
[0037] The present invention also provides a membrane electrode for proton exchange membrane water electrolysis, including an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer. Wherein, the anode catalyst layer can be prepared by the above-mentioned anode catalyst slurry through a film-forming treatment method such as an ultrasonic spraying method or a doctor blade method. The present invention has no special restrictions on the cathode catalyst layer and the proton exchange membrane, and it can be a conventional choice for those skilled in the art. For example, the cathode catalyst layer can be prepared by a slurry including a cathode catalyst Pt / C by an ultrasonic spraying method, and the proton exchange membrane can select a Nafion 115 proton exchange membrane. The obtained membrane electrode can be applied to a device for hydrogen production by proton exchange membrane water electrolysis, so the present invention also provides a device for hydrogen production by proton exchange membrane water electrolysis, such as a proton exchange membrane water electrolysis hydrogen production electrolytic cell, including the anode catalyst, anode catalyst slurry or membrane electrode involved in the above technical solution.
[0038] Through research, it was found that the electrolytic cell assembled using the anode catalyst provided by the present invention had excellent catalytic activity and operating stability through corresponding tests, and the loading amount of the precious metal Ir was greatly reduced.
[0039] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention can be purchased from the market or prepared according to conventional preparation methods well known to those skilled in the art.
[0040] Example 1
[0041] This embodiment provides an IrOx / Ti4O7@TiO2, and the preparation method thereof is as follows:
[0042] At room temperature, 105 mg of Ti4O7 carrier with an average particle size of 100 nm and 516 mg of CTAB were added to 50 mL of ethylene glycol and ultrasonically dispersed for 1 h; 3 mL of 15 mg Ir mL -1 Chloroiridic acid solution was stirred at room temperature for 0.5 h; refluxed at 140 °C for 6 h, cooled to room temperature, washed five times by centrifugation with water, and dried under vacuum at 55 °C for 12 h to obtain a black powder 1; 100 mg of the black powder 1 was placed in a muffle furnace and heated at 5 °C for 12 h. -1 The product was IrOx / Ti4O7@TiO2 and heat treated at 350℃ in air atmosphere for 0.5h at a heating rate of .
[0043] The IrOx / Ti4O7@TiO2 catalyst of Example 1 was characterized by electron microscopy. Figure 1-2 As shown, Figure 1 This is the SEM image of IrOx / Ti4O7@TiO2 catalyst. Figure 2TEM image of IrOx / Ti4O7@TiO2 catalyst. Figures 1-2 It can be seen that IrOx / Ti4O7@TiO2 is still a particle with a particle size of about 100nm. TEM observation shows that there is a uniform distribution of IrOx nanoparticles on the surface without obvious agglomeration.
[0044] The IrOx / Ti4O7@TiO2 catalyst of Example 1 was subjected to X-ray diffraction analysis and the results are as follows: Figure 3 As shown, the diffraction peaks in IrOx / Ti4O7@TiO2 include a peak corresponding to IrO2, a sharp peak corresponding to TiO2 and multiple diffraction peaks corresponding to Ti4O7, indicating that the catalyst does contain a carrier Ti4O7 and IrO2 and TiO2 loaded on the carrier.
[0045] Using the IrOx / Ti4O7@TiO2 of Example 1 as the anode catalyst, a proton exchange membrane water electrolysis hydrogen production electrolytic cell was assembled, and the obtained steady-state polarization curve is as follows: Figure 4 As shown in the figure, it has lower Ir loading and higher catalytic activity compared with Elyst Ir75 0520 catalyst produced by Umicore.
[0046] Using the IrOx / Ti4O7@TiO2 of Example 1 as the anode catalyst, a proton exchange membrane water electrolysis hydrogen production electrolytic cell was assembled, and its stability test curve is as follows: Figure 5 As shown, it can be seen that it has excellent long-term operating stability.
[0047] Example 2
[0048] This embodiment provides an IrOx / Ti4O7@TiO2, and the preparation method thereof is as follows:
[0049] At room temperature, 90 mg of Ti4O7 carrier with an average particle size of 100 nm and 362 mg of CTAB were added to 100 mL of ethylene glycol and ultrasonically dispersed for 0.5 h; 4.2 mL of 15 mg Ir mL -1 Potassium chloroiridate solution was stirred at room temperature for 0.5 h; refluxed at 150 °C for 5 h, cooled to room temperature, washed five times by centrifugation with ethanol, and dried under vacuum at 55 °C for 12 h to obtain a black powder 1; 200 mg of the black powder 1 was placed in a muffle furnace at 4 °C for 1 h. -1 At a heating rate of , the product was heat treated at 320 °C in air atmosphere for 0.5 h, namely IrOx / Ti4O7@TiO2.
[0050] The IrOx / Ti4O7@TiO2 of Example 2 was characterized by electron microscopy, analyzed by X-ray diffraction spectrum, and tested for membrane electrode performance. The results were similar to those of Example 1.
[0051] Example 3
[0052] This embodiment provides an IrOx / Ti4O7@TiO2, and the preparation method thereof is as follows:
[0053] At room temperature, 100 mg of Ti4O7 carrier with an average particle size of 150 nm and 423 mg of CTAB were added to 150 mL of ethylene glycol and ultrasonically dispersed for 2 h; 50 mg of iridium trichloride was added, ultrasonicated for 0.5 h, and stirred at room temperature for 2 h; refluxed at 160 ° C for 4 h, cooled to room temperature, washed five times by centrifugation with a mixture of water and ethanol, and vacuum dried at 55 ° C for 12 h to obtain a black powder 1; 200 mg of the black powder 1 was placed in a muffle furnace and heated at 4 ° C min -1 At a heating rate of , the product was heat treated at 320 °C in air atmosphere for 0.5 h, namely IrOx / Ti4O7@TiO2.
[0054] The IrOx / Ti4O7@TiO2 of Example 3 was characterized by electron microscopy, analyzed by X-ray diffraction spectrum, and tested for membrane electrode performance. The results were similar to those of Example 1.
[0055] Example 4
[0056] This embodiment provides an IrOx / Ti4O7@TiO2, and the preparation method thereof is as follows:
[0057] At room temperature, 200 mg of Ti4O7 carrier with an average particle size of 100 nm and 423 mg of CTAB were added to 150 mL of ethylene glycol and ultrasonically dispersed for 2 h; 100 mg of potassium chloroiridate was added, ultrasonicated for 0.5 h, and stirred at room temperature for 2 h; refluxed at 160 ° C for 3 h, cooled to room temperature, washed with water by centrifugation five times, and vacuum dried at 55 ° C for 12 h to obtain a black powder 1; 200 mg of the black powder 1 was placed in a muffle furnace and heated at 4 ° C min -1 At a heating rate of , the product was heat treated at 320 °C in air atmosphere for 0.5 h, namely IrOx / Ti4O7@TiO2.
[0058] The IrOx / Ti4O7@TiO2 of Example 4 was characterized by electron microscopy, analyzed by X-ray diffraction spectrum, and tested for membrane electrode performance. The results were similar to those of Example 1.
[0059] Example 5
[0060] This embodiment provides an IrOx / Ti4O7@TiO2, and the preparation method thereof is as follows:
[0061] At room temperature, 150 mg of Ti4O7 carrier with an average particle size of 100 nm and 678 mg of CTAC were added to 200 mL of ethylene glycol and ultrasonically dispersed for 2 h; 100 mg of iridium acetate was added, ultrasonicated for 0.5 h, and stirred at room temperature for 2 h; refluxed at 180 ° C for 2 h, cooled to room temperature, washed five times by centrifugation with ethanol, and vacuum dried at 55 ° C for 12 h to obtain a black powder 1; 100 mg of the black powder 1 was placed in a muffle furnace and heated at 1 ° C min -1 The product was IrOx / Ti4O7@TiO2 and heat treated at 200℃ in air atmosphere for 0.5h at a heating rate of .
[0062] The IrOx / Ti4O7@TiO2 of Example 5 was characterized by electron microscopy, analyzed by X-ray diffraction spectrum, and tested for membrane electrode performance. The results were similar to those of Example 1.
[0063] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A proton exchange membrane water electrolysis anode catalyst, characterized in that: It includes a carrier Ti4O7 and IrOx and TiO2 loaded on the Ti4O7; Among them, 1<x≤2; The proton exchange membrane water electrolysis anode catalyst is prepared according to the following method: The Ti4O7 loaded with elemental iridium is heat treated at 200-600° C. to obtain the anode catalyst.
2. The proton exchange membrane water electrolysis anode catalyst according to claim 1, characterized in that: The mass ratio of IrOx to Ti4O7 is (0.1~4):
1.
3. The method for preparing a proton exchange membrane water electrolysis anode catalyst according to claim 1 or 2, characterized in that: The following steps are involved: The Ti4O7 loaded with elemental iridium is heat treated at 200-600° C. to obtain the anode catalyst.
4. The preparation method according to claim 3, characterized in that: The atmosphere of the heat treatment is air atmosphere.
5. The preparation method according to claim 3, characterized in that: The heating rate of the heat treatment is 0.5-10°C / min.
6. The preparation method according to claim 3, characterized in that: The heat treatment time is 0.5 to 24 h.
7. The preparation method according to claim 3, characterized in that: The Ti4O7 loaded with elemental iridium is prepared by a polyol reduction method or a hydrogen reduction method.
8. A proton exchange membrane water electrolysis anode catalyst slurry, characterized in that: including anode catalyst, dispersant, binder and solvent; The anode catalyst is the anode catalyst for proton exchange membrane water electrolysis according to claim 1 or 2, or the anode catalyst for proton exchange membrane water electrolysis prepared by the preparation method according to any one of claims 3 to 7.
9. A membrane electrode for proton exchange membrane water electrolysis, characterized in that: It includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer; The anode catalyst layer is prepared by subjecting the anode catalyst slurry according to claim 8 to a film-forming treatment.
10. A proton exchange membrane water electrolysis hydrogen production electrolytic cell, characterized in that: The invention comprises the anode catalyst according to claim 1 or 2, the anode catalyst prepared by the preparation method according to any one of claims 3 to 7, the anode catalyst slurry according to claim 8 or the membrane electrode according to claim 9.
Citation Information
Patent Citations
Corrosion-resistant metal oxide-based composite material as well as preparation method and application thereof
CN112973680A
Anti-antipolar catalyst for proton exchange membrane fuel cell and preparation method of anti-antipolar catalyst
CN114520343A